Academic Licence of Software Tools Created for Education in the Field of Railway Vehicles at the University of Pardubice (Current Problems in Rail Vehicles, 2021)
A couple of software tools for use in the educational process in the field of railway vehicles are presented in this paper. Both of them were created as an academic licence at the Faculty of Transport Engineering of the University of Pardubice (Czech Republic). In the first case, the simulation tool “SJKV-V4N v. 1.0” was created in framework of the project “Competence Center of Railway Vehicles” of the Technology Agency of the Czech Republic in 2018. This software represents a particular version of the multi-body simulation tool “SJKV”, which was supplemented with a user interface, and nowadays it is available for non-commercial use by the students and academic staff for free. It is intended for realization of multi-body simulations of three pre-defined design concepts of four-axle railway vehicles under certain conditions. The second software tool – named as “RailCalc 2.0” – is intended for traction calculations,i.e., for the calculations of running times and energy consumption of defined trains on defined railway lines. This software  represents a modified version of the program “RailCalc” created in framework of a bachelor thesis at the Faculty of Transport Engineering in 2020.
Keywords: railway vehicles; multi-body simulation; traction calculation; software; SJKV; RailCalc